Code-Switching and Code-Mixing in African Creative Writing: Some Insights for Translation Studies - Bandia, Paul (TTR, 1996)
AbstractCode-Switching and Code-Mixing in African Creative Writing: Some Insights for Translation Studies — A characteristic feature of African creative writing is the use of code-switching and code-mixing as a writing technique. Code-switching and code-mixing have a discourse, referential and sociolinguistic significance in a text. This paper deals with how African writers use various forms of code-switching and code-mixing as linguistic choices having specific pragmalinguistic functions in a text. Our aim is to show how exploiting this type of 'language mixing' for literary creativity calls for specific translation strategies and, how translating code-switched and code-mixed texts requires techniques that can help us enhance our knowledge of the translation process.